2008
DOI: 10.1007/s10637-008-9134-3
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian marine sponge Polymastia janeirensis induces apoptotic cell death in human U138MG glioma cell line, but not in a normal cell culture

Abstract: Marine sponges have been prominently featured in the area of cancer research. Here, we examined the anti-proliferative effects of crude extracts (aqueous and organic) of the Brazilian marine sponge Polymastia janeirensis in the U138MG human glioma cell line. Moreover, we examined the effects of extracts on selective cytotoxicity in the glioma cells in comparison with a normal cell culture. Exposure of glioma cells to treatments (24 h) resulted in cell number decrease at all doses tested, with both aqueous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 48 publications
(47 reference statements)
2
7
0
Order By: Relevance
“…So far, sterols and tetrahydroxyamide have been reported in the genus Polymastia (Da Frota et al 2009), which are in general agreement with the metabolites detected in P. nigra in this study (Table 2).…”
Section: Natural Product Research 315supporting
confidence: 92%
See 1 more Smart Citation
“…So far, sterols and tetrahydroxyamide have been reported in the genus Polymastia (Da Frota et al 2009), which are in general agreement with the metabolites detected in P. nigra in this study (Table 2).…”
Section: Natural Product Research 315supporting
confidence: 92%
“…Recent reports demonstrated that the extracts from Polymastia janeirensis exhibited a selective cytotoxic effect on glioma cells compared with a normal cell culture (Da Frota et al 2009), which is similar to our results with P. nigra, but against HeLa cells. So far, sterols and tetrahydroxyamide have been reported in the genus Polymastia (Da Frota et al 2009), which are in general agreement with the metabolites detected in P. nigra in this study (Table 2).…”
Section: Natural Product Research 315supporting
confidence: 91%
“…Yet, aqueous extracts significantly retarded the migration of polymorphonuclear leukocytes in a chemotactic assay [13]. In other work, an in vitro antiviral activity was observed against the simian rotavirus RV-SA11 with aqueous extract of P. janeirensis [14], and more recently, we reported that aqueous and organic extracts of this marine sponge induced apoptotic cell death in human U138MG glioma cell line, but not in a normal cell culture [15]. This is particularly important because malignant gliomas are characterized by an intrinsic resistance to apoptosis [16].…”
Section: Introductionmentioning
confidence: 51%
“…Cells were kept at 37°C in a humidified atmosphere with 5% CO 2 . Astrocyte cultures were prepared as previously described by Da Frota et al ( 23 ). Briefly, cortex of newborn Wistar rats (1–3 days old) were removed and dissociated mechanically in Ca +2 and Mg +2 -free balanced salt solution (CMF) (pH 7.4) containing 137 mM NaCl, 5.36 mM KCl, 0.27 mM Na 2 HPO 4 , 1.1 mM KH 2 PO 4 , and 6.1 mM glucose.…”
Section: Methodsmentioning
confidence: 99%